2015
DOI: 10.1590/1678-7457
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic shears and bipolar vessel-sealing system for three-port laparoscopic ovariohysterectomy in dogs

Abstract: In the current experimental study, two different instruments were compared for prophylactic hemostasis during a 3-port technique of laparoscopic ovariohysterectomy (OVH) in bitches. Moreover, the need for port enlargement for specimen retrieval using 5mm or 10mm trocartes, technical difficulties and complications were assessed. Ultrasonic energy and a vascular sealing system were tested. Duration of surgery, patient weight and diameter of the uterine arteries and veins were compared among the groups. Fifteen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Classification of studies by organ system is presented in Tables S1 and S2. Numbers of studies and participants were reported within each organ/system group including female genital tract (22 studies [n = 1407 dogs]), 1,7,11,20,30‐47 urinary tract (7 studies [n = 114]), 3,48‐53 stomach (9 studies [n = 250]), 10,18,54‐59 intestinal tract (5 studies [n = 48]), 60‐64 liver (5 studies [n = 288]), 12,17,65‐67 adrenal gland (5 studies [n = 62]), 13,28,68‐70 spleen (7 studies [n = 111]), 19,71‐76 and other (4 studies that included gastropexy and ovariectomy procedures [n = 148]) 9,77‐79 . One experimental study, in which colopexy in seven male dogs was described, was classified as intestinal tract even though these dogs were also sterilized during the surgical procedure because this study reported only complications and outcomes related to colopexy 63 .…”
Section: Resultsmentioning
confidence: 99%
“…Classification of studies by organ system is presented in Tables S1 and S2. Numbers of studies and participants were reported within each organ/system group including female genital tract (22 studies [n = 1407 dogs]), 1,7,11,20,30‐47 urinary tract (7 studies [n = 114]), 3,48‐53 stomach (9 studies [n = 250]), 10,18,54‐59 intestinal tract (5 studies [n = 48]), 60‐64 liver (5 studies [n = 288]), 12,17,65‐67 adrenal gland (5 studies [n = 62]), 13,28,68‐70 spleen (7 studies [n = 111]), 19,71‐76 and other (4 studies that included gastropexy and ovariectomy procedures [n = 148]) 9,77‐79 . One experimental study, in which colopexy in seven male dogs was described, was classified as intestinal tract even though these dogs were also sterilized during the surgical procedure because this study reported only complications and outcomes related to colopexy 63 .…”
Section: Resultsmentioning
confidence: 99%